Usborne illustrated elementary math dictionary - Rogers, Kirsteen; Large, Tori; Tomlins, Karen; Ebbutt Sheila; Russel, Ruth; Armstrong, Carrie A. (New York : Scholastic, 2010)
Defines key terms and concepts dealing with numbers and number facts, calculations, shape and space, measurements, and data.
Keywords: Usborne Math Dictionary -- non-fiction